Plantetablering och tillväxt för sådd och planterad tall 2-5 år efter markberedning med harv eller Huminmix-teknik inom Holmen Skog distrikt Norsjö - Åström, Håkan (2006)
The objective of this work was to compare the environmentally gentle soil scarification technique Huminmix (with possibilities to do track-grinding/HMMspår, long-scraping/HMMlångfläck and mounding/HMMhög) with conventional disc trencher, concerning seedling establishment and growth of direct seeded and planted Scots pine seedlings. Inventories were made during June and July 2005, in 34 seeded and 6 planted stands from 2000 – 2004 (1- 5 years old) of lichen- and myrtillus/vaccinum-type in Holmen Skog AB´s district Norsjö in Västerbotten. The Huminmix-technique had been used for HMMspår in the seeded stands and for HMMhög in the planted stands (HMMlångfläck has been used from the year 2006 for direct seeding). The studied stands had been seeded with the same amount of seeds according to stand data. The seeding-technique was expected to work equally efficient for the disc trencher- and Huminmix-method. The stands were selected as pares, i.e., one stand scarified with disc trencher was selected for each stand scarified with Huminmix. The pares were selected so that site index, vegetation type, ground conditions, soil moisture, m.a.sl., exposition, etc., were as equal as possible. In each stand 20 sample plots were inventoried. Each sample plot was represented by 1 meter in the scarified track in the seeded stands while the planted stands were inventoried by using circle plots (1.78 m radius). All the stands scarified by disc trencher and Huminmix-technique were regarded as more than in compliance with the forest act (§ 6). The number of plants per ha after sowing was generally high for both vegetation types (5000 – 15000 per hectar). No scarification method had significantly more vigorous plants per meter scarification than the other in stands sown in 2000 – 2002. Disc trencher had generally higher plant establishment than HMMspår, with a significant difference in 2003. However, this difference was according to the scarification entrepreneur probably caused by the seeding equipment that was changed this year (too few seed were sown at low advance speed). Since the seeding technique of today spreads the seeds relatively wide, the wider patches of the disc trencher reduces the risk for the seed to land beside the scarified patch. The percent disturbed soil surface was more than double for the disc trencher (approx. 30 % + the width of the ridge), compared to HMMspår (approx. 15 %). HMMspår-stands had significantly higher (approx. 40 %) vigorous plants per scarified square meter compared with disc trencher stands in 2000 and 2001 for both lichen- and myrtillus/vaccinum-type. This indicates that the Huminmix technique creates a good substrate for seedling establishment. The disc trencher had brought about significantly higher plant growth (approx. 40 %) in stands of lichen type for seed year 2000 (the situation was the opposite in 2001 but not significant) and in stands of myrtillus/vaccinum-type for seed year 2000 and 2001. Regression analyses suggest a positive relation, presumably related to temperature, between track width and plant growth for stand seeded in 2000 and 2001. This could explain the differences in growth between the two scarification methods. In the planted stands there were no difference between the to scarification methods concerning vigorous plants per hectare. Stands planted in the year 2001 had brought about 20 % higher plant growth after scarification with Huminmix technique compared to disc trencher. The setting HMMspår is environmentally gentle and results in better plant establishment per square meter of scarified area compared to the disc trencher. The disc trencher technique, in combination with the used seeding equipment, of today seems to result in somewhat higher numbers of seedlings per hectare. The disc trencher seems to result in better plant growth regardless of vegetation type 4 – 5 years after seeding compared to HMMspår with the track width used in the stand inventoried while mounding with Huminmix technique (HMMhög) seems to result in improved early growth compared to disc trencher, in planted stands. The humus thickness seems to affect plant establishment after direct seeding more if HMMspår is used instead of disc trencher. The Huminmix technique therefore could be used differently than today when sowing. HMMlångfläck should be used to a greater extent on soils with thicker humus layer because it leads to higher exposition of mineral soil/heat. Another alternative could be to use wider wheels that make the scarified track wider. It would be possible to reduce the number of sown seeds and at the same time retain a good plant establishment if the seed release is improved. When planting the setting HMMhög seems to work fine as it is used today. The place of the Huminmix-technique in Holmen Skog´s decision support for selection of scarifying technique depends on whether the reforestation method is planting or sowing. The flexible construction that makes it possible for the Huminmix to change from narrow grind tracks to more radical 2.5 m long scraped patches, to mounding makes it possible to use it in several types of stands. HMMspår should be used for sowing in areas with thin humus thickness, and especially in areas with reindeer herding. HMMlångfläck is probably more suitable for sowing (and possible natural regeneration) on soils with thicker humus layer and HMMhög should be used in areas where patch scarification or disc trencher normally is used for planting.